2010
DOI: 10.3758/s13421-010-0005-8
|View full text |Cite
|
Sign up to set email alerts
|

Inoculating against eyewitness suggestibility via interpolated verbatim vs. gist testing

Abstract: In real-life situations, eyewitnesses often have control over the level of generality in which they choose to report event information. In the present study, we adopted an early-intervention approach to investigate to what extent eyewitness memory may be inoculated against suggestibility, following two different levels of interpolated reporting: verbatim and gist. After viewing a target event, participants responded to interpolated questions that required reporting of target details at either the verbatim or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
47
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 71 publications
4
47
0
Order By: Relevance
“…Drawing from both practical and theoretical considerations, we extended Pansky and Tenenboim's (2011) approach in the current experiment. More specifically, we examined the effect of meaning versus item‐specific testing on the susceptibility to misinformation from a developmental angle.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…Drawing from both practical and theoretical considerations, we extended Pansky and Tenenboim's (2011) approach in the current experiment. More specifically, we examined the effect of meaning versus item‐specific testing on the susceptibility to misinformation from a developmental angle.…”
mentioning
confidence: 98%
“…Researchers argue that taking a test strengthens the memory trace for a specific event, which in turn reduces the impact of forgetting and external misinformation (e.g., Chan, Thomas, & Bulevich, 2009). In support of the protective value of testing, studies have frequently found an inoculation effect against misinformation (e.g., Pansky & Tenenboim, 2011; Wang, Paterson, & Kemp, 2014). In one of these studies, participants filled out the SAI immediately after seeing a video of a robbery (Gabbert, Hope, Fisher, & Jamieson, 2012, Experiment 1).…”
mentioning
confidence: 99%
See 3 more Smart Citations